EPILEPSY SURGERY IN PATIENTS WITH TUBEROUS SCLEROSIS - Hans Holthausen; Tom Pieper; Hans Eitel; Manfred Kudernatsch (Русский журнал детской неврологии)
With a few exceptions patients with tuberous sclerosis (TS) suffering from drug-resistant epilepsies have potentially epileptogenic lesionswithin both hemispheres. Until one decade ago in general such a constellation was an xclusion criteria for considerations with respect to epilepsy surgery. However experience has shown that it is not so rare to find patients in whom over the ears seizures are generated from just one single focus and that these patients can be good candidates for epilepsy surgery. Almost revolutionary was the further evelopment: multi-step procedures in patients with bilateral epileptogenic lesions – with promising results in terms of postoperative seizure outcome. Also, with increasing experience, it becomes more and more possible to differentiate already non-invasively which lesions could be epileptogenic and which are rather not the source of the seizures. The most important achievement of epilepsy surgery in TS however is that in selected cases early surgical intervention is able to prevent severe mental retardations, which are often the main burden for families who have members with this peculiar disease.